PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN ORGANIZATIONAL CITIZEN BEHAVIOR TERHADAP KINERJA KARYAWAN PADA PT. BNI CABANG PALU - Magfirah, Magfirah (Katalogis, 2015)
Abstract The study intends to seek and analyze simultaneous and partial influence of transformational leadership style, motivation, and organizational citizenship behavior on employees’ performance at PT. Bank Negara Indonesia (Persero) Tbk, The Main Office of Palu. The study involves 80 personnel of PT. Bank Negara Indonesia (Persero) Tbk, The Main Office of Palu as respondents. Method of analysis used is explanatory research with Multiple Linear Regressions. The results show that transformational leadership style, motivation, and organizational citizenship behavior simultaneously and partially have significant influence on employees’ performance at PT. Bank Negara Indonesia (Persero) Tbk, The Main Office of Palu.